PENGARUH VARIASI KONSENTRASI EKTRAK KULIT BUAH KETAPANG (Terminalia Catappa) TERHADAP LAJU KOROSI PADA BESI ASTM A36 - Prabowo, Ocean; Syafriadi, Syafriadi; Suka, Ediman Ginting (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The aim of this study was to investigate the influence of varying concentrations of Terminalia catappa fruit peel extract on the corrosion rate during immersion periods of 2 days, 4 days, and 6 days for ASTM A36 steel. The ASTM A36 steel specimens were immersed in a corrosive medium containing 2% NaCl, with inhibitor compositions of 0%V, 1%V, 2%V, and 3%V being tested. Measurement results revealed that as the concentration of Terminalia catappa fruit peel extract increased, the corrosion rate proportionally decreased. The lowest corrosion rate was observed in samples with a 3%V inhibitor composition, subjected to a 4-day immersion, measuring at 0.02321 mmpy. Moreover, with the augmentation of fruit peel extract concentration, inhibition efficiency exhibited an augmented trend (83.02% for the 3%V composition, and the lowest at 41.84% for the 1%V composition).